2008
DOI: 10.5032/jae.2008.04083
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Influence the Decision to Participate in Youth Organizations in Rural High Schools in Three States

Abstract: This study sought to determine the factors that influenced student decisions to participate in FFA in a rural school and their level of involvement as an FFA member. Data was collected from 2,111 high school students in 41 rural high schools in Arizona, Florida, and Texas. Discriminant analysis identified four factors that influence participation in FFA in the respondents: high school GPA, participation in on-campus (non-Career/Technical organizations) activities, agreement with the statement "Leadership activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…Students from rural areas had increased participation and knowledge compared to those from urban areas; this was a noteworthy point, possibly indicating a higher level of inquisitiveness. This is also in agreement with the observations of Rayfield et al (2008) and Croft and Moore (2019), who observed that rural students participate more in extracurricular activities than their urban counterparts [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…Students from rural areas had increased participation and knowledge compared to those from urban areas; this was a noteworthy point, possibly indicating a higher level of inquisitiveness. This is also in agreement with the observations of Rayfield et al (2008) and Croft and Moore (2019), who observed that rural students participate more in extracurricular activities than their urban counterparts [ 34 , 35 ].…”
Section: Discussionsupporting
confidence: 92%
“…FFA is currently one of the largest youth development organizations in U.S. public schools and is considered a key component in providing positive youth development opportunities to students enrolled in SBAE (National FFA Organization, 2015;Rayfield, Compton, Doerfert, Fraze, & Akers, 2008). FFA is structured in such a way that it provides opportunities for young adults to achieve personal goals and engage in meaningful activities (Croom & Flowers, 2001).…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…Student involvement is a measure of physical and psychological energy students devote to their experiences (Astin, 1999). Rayfield et al, (2008) reported 5 postulates from Astin's student involvement theory: (a) involvement refers to the investment of physical and psychological energy in various objects; (b) regardless of the object, involvement occurs along a continuum; (c) involvement has both quantitative and qualitative features; (d) the amount of student learning and personal development associated with any educational program is directly proportional to the quality and quantity of student involvement in that program; and (e) the effectiveness of any educational policy or practice is directly related to the capacity of that policy or practice to increase student involvement. (p. 85) Quantifying successful programs throughout the three circle model is paramount to identifying important characteristics for further investigation.…”
Section: Theoretical/conceptual Frameworkmentioning
confidence: 99%
“…The study of why students choose to participate in agricultural activities has a long history (Rayfield, Compton, Doerfert, Fraze, & Akers, 2008). Youth might be motivated to participate in a programme for many different reasons.…”
Section: Predictors Of Youth Participation In Voluntary Programmesmentioning
confidence: 99%
“…FFA members believed that the agriculture teacher had an influence on their decision to enrol and participate in agricultural activities. In another study conducted by Rayfield et al (2008) there were a few factors that influenced youth participation in FFA; high school Grade Point Average (GPA), participation in on-campus activities, agreement with the statement "Leadership activities have made me a more confident person," and which school year the students belong to. According to the Harvard Family Research Project (2004), older youth may participate in community programmes only when they are offered a flexible schedule for particular days or times.…”
Section: Predictors Of Youth Participation In Voluntary Programmesmentioning
confidence: 99%